1994
DOI: 10.1021/bi00173a025
|View full text |Cite
|
Sign up to set email alerts
|

The Actual Incision Determines the Efficiency of Repair of Cisplatin-Damaged DNA by the Escherichia coli UvrABC Endonuclease

Abstract: The UvrABC endonuclease from Escherichia coli repairs a broad spectrum of DNA lesions with variable efficiencies. The effectiveness of repair is influenced by the nature of the lesion, the local DNA sequence, and/or the topology of the DNA. To get a better understanding of the aspects of this multistep repair reaction that determine the effectiveness of repair, we compared the incision efficiencies of linear DNA fragments containing either a site-specific cis-[Pt(NH3)2(d(GpG)-N7(1),-N7(2)]] or a cis- Pt(NH3)2[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 42 publications
(60 reference statements)
5
40
0
Order By: Relevance
“…Several observations have suggested that the resulting UvrB-DNA preincision complex is stable in the presence of ATP only: (i) Isolation of UvrB-DNA complexes by column chromatography at room temperature was only possible if the chromatography buffers contained ATP (9). (ii) Separation of preincision complexes by gel retardation results in a much higher yield when ATP is included in the gel and the electrophoresis buffer (10,17). In this paper we show that a stable UvrB-DNA complex can be isolated in the absence of ATP by capture of a biotinylated damaged DNA substrate on streptavidin-coated magnetic beads.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several observations have suggested that the resulting UvrB-DNA preincision complex is stable in the presence of ATP only: (i) Isolation of UvrB-DNA complexes by column chromatography at room temperature was only possible if the chromatography buffers contained ATP (9). (ii) Separation of preincision complexes by gel retardation results in a much higher yield when ATP is included in the gel and the electrophoresis buffer (10,17). In this paper we show that a stable UvrB-DNA complex can be isolated in the absence of ATP by capture of a biotinylated damaged DNA substrate on streptavidin-coated magnetic beads.…”
Section: Discussionmentioning
confidence: 84%
“…Protein Purifications-The UvrA, UvrB, and UvrC proteins were purified as described (10). Mutant proteins UvrC (D466A) (11), UvrC(L221PϩF223L) (12), UvrB(G509S), and UvrB(R544H) (8) have been described and were purified according to the same procedure as the wild type proteins.…”
Section: Methodsmentioning
confidence: 99%
“…All these results suggest that the UvrAB recognition and UvrC incision steps might obey different binding criteria. The recognition would work for bent DNA structures as well as for any type of adducts, particularly with bulky hydrophobic groups, whereas incision would be more sensitive to the DNA sequence and the torsional constraint (39).…”
Section: Discussionmentioning
confidence: 99%
“…UvrA, wild type UvrB, UvrBK45A, and SSB were overexpressed and purified as described (33,(53)(54)(55).…”
Section: Methodsmentioning
confidence: 99%